The effect of nutrition counseling on growth development and success in star wrestlers: Nutrition counseling and star wrestlers - Sökülmez Kaya, Pınar; Ulus, Canan Asal (Progress in Nutrition, 2021)
ABSTRACT: The aim of this study is to investigate the feeding habits of national wrestlers. 36 volunteer male newcomer national wrestlers who were between 13-15 years old participated in the study. One group of the wrestlers in two different regions of the same age was given nutrition education and nutrition counseling by the researcher for one year. The obtained data were saved to the computer using SPSS 13.5 package program. In all tests, p